Liquid Modernity at Zygmunt Baumann and its Reflections on the types of crimes in Jordanian Society from the point of view of competent people - Al-Rusaifan, Hind Mohammed Hameid; Al-Habarneh, Najah Hussein (Journal of Humanities & Social Sciences, 2022)
This study aimed to find out the effect of the reflection of the fluidity of modernity in its theoretical concepts by the polish sociologist zygmunt baumann on the quality of crimes in Jordanian society . from the study sample , specialized faculty members working in public and private Jordanian universities , which include specialization (sociology , criminology , criminology and deviation , social service and social work) , as it was found by the researcher that these disciplines do not exist in private universities and are limited to some public universities it is the university of Jordan , mutah university , and al-balqa applid university through some of its affiliated community colleges , in addition to yarmouk university and al-hussein university , which number (58) faculty members , according to the statistics of the ministry of higher education and scientific research for the year 2021 . the study concluded that the general level reflects the manifestation of zygmunt baumanns fluid modernity on the types of crime in Jordanian society the effect was average , where the appearance of the work came in the first order at a high level , then liberation also at a high level , and then “time and place” at an average level , followed by the appearance of individuality at a medium level and the group at a medium level , where there is a gradual and average rise in the quality of crimes in society , and the study concluded with sevral results , which are a clear reflection of the manifestations of modernity according to zygmunt baumann (liberation , individuality , time/place , work , and group) on the quality of crimes in Jordanian society , as they formed modern manifestation that society began to touch in all aspects of its economic and social life through the huge amount of technological development in software and technologies , which contributed the existence of a qualitative process of human communication that allowed criminals to exploit this development to conceal and obliterate the features and effects of the crime , in the murder cases that are reported as suicide incidents , the detection and investigation of their circumstances by the security services contributed with forensic reports and the presence of criminal suspicion , and the increasing number of violent crimes inside the family and reconsideration of the lows that must provide protection for women , children and eldery and redress for all those who are subjected to any from of oppression this violence and the non-acceptance of dropping the personal right by the judiciary to any victim ,the necessity of punishing the offender and achieving justice through deterrent penalties , and intensifying awareness and education programs in schools and universities on the importance of the family and its role in building a good and giving person , the role of institutions of upbringing and societal values that maintain the cohesion of human groups and how solving problems and how to deal with disagreements and disputes in a way that enhances legal concepts and confidence in resorting to the judiciary.